Proceedings of the XVI International Numismatic Congress, 11–16.09.2022, Warsaw: Vol. II. Roman Numismatics (Brepols, 2026)
The XVI International Numismatic Congress, held in Warsaw, Poland, in September 2022, was a landmark event, drawing the largest number of participants in its history. With over 550 papers presented during thematic sessions and round tables, this congress showcased the latest advancements and research in the field of numismatics from leading experts and scholars in their field. A curated selection of papers from the conference have now been drawn together into peer-reviewed conference proceedings, representing a comprehensive spectrum of numismatic studies from antiquity to modern times. Each paper is meticulously illustrated with high-quality images, often of unique specimens, along with detailed diagrams, maps, and die/typological chains. Topics covered include coins and coin finds, medals, tokens, banknotes, the history of collections and collecting, and cutting-edge chemical analyses and technologies used in coin examination. This volume, the second in four thematic volumes, focuses on Roman coinage. Divided into two separate volumes, covering respectively forty-four chapters on coinage and forty on circulation, the contributions gathered here explore not only Rome and the Imperial mints, but also local phenomena from Spain to Asia Minor, including graffiti, imitations, and copies of Roman coinage.